Overweight, obesity and excessive weight gain in pregnancy as risk factors for adverse pregnancy outcomes: A narrative review. Issue 2 (20th March 2022) - Langley‐Evans, Simon C.; Pearce, Jo; Ellis, Sarah
Abstract: The global prevalence of overweight and obesity in pregnancy is rising and this represents a significant challenge for the management of pregnancy and delivery. Women who have a pre‐pregnancy body mass index greater than 25 kg m –2 are more likely than those with a body mass index in the ideal range (20–24.99 kg m –2 ) to have problems conceiving a child and are at greater risk of miscarriage and stillbirth. All pregnancy complications are more likely with overweight, obesity and excessive gestational weight gain, including those that pose a significant threat to the lives of mothers and babies. Labour complications arise more often when pregnancies are complicated by overweight and obesity. Pregnancy is a stage of life when women have greater openness to messages about their lifestyle and health. It is also a time when they come into greater contact with health professionals. Currently management of pregnancy weight gain and the impact of overweight tends to be poor, although a number of research studies have demonstrated that appropriate interventions based around dietary change can be effective in controlling weight gain and reducing the risk of pregnancy complications. The development of individualised and flexible plans for avoiding adverse outcomes of obesity in pregnancy will require investment in training of health professionals and better integration into normal antenatal care. Highlights: Overweight and obesity before pregnancy and excessive gestational weight gain are major determinants of risk for pregnancy loss, gestational diabetes, hypertensive conditions, labour complications and maternal death. Pregnancy is regarded as a teachable moment when women are at their most receptive to messages about their health. However, unclear guidance on diet and physical activity, weight stigma from health professionals, inexperience and reluctance among professionals about raising issues about weight, and stretched resources put the health of women and babies at risk. Excessive weight gain in pregnancy and post‐partum weight retention compromise future fertility and increase risk for future pregnancies. Large randomised controlled trials have had little success in addressing excessive gestational weight gain or antenatal complications. Individualised, culturally sensitive and responsive interventions appear to have greater success. Abstract : Overweight and obesity complicate up to two‐thirds of pregnancies, and increase risk of gestational diabetes, hypertension, pre‐eclampsia, and maternal and fetal death. Interventions to reduce risk can be effective but will require improved protocols to discuss weight with pregnant women and enhanced training for midwives to deliver appropriate guidance on lifestyle change.